2018
DOI: 10.1007/s11060-018-2804-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of the long-term use of temozolomide for treating newly diagnosed glioblastoma in Germany

Abstract: Concomitant radiochemotherapy followed by six cycles of temozolomide (= short term) is considered as standard therapy for adults with newly diagnosed glioblastoma. In contrast, open-end administration of temozolomide until progression (= long-term) is proposed by some authors as a viable alternative. We aimed to determine the cost-effectiveness of long-term temozolomide therapy for patients newly diagnosed with glioblastoma compared to standard therapy. A Markov model was constructed to compare medical costs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The examinations and treatments of GBM are expensive and represent a significant economic burden on health care system all around the world 47 . Compare with liquid biopsy, molecular test, and advanced magnetic resonance imaging (MRI) examination, blood biomarkers such like AAPR, NLR, platelet to lymphocyte ratio (PLR), and lymphocyte to monocyte ratio (LMR) are convenient, cheap, and time-saving.…”
Section: Discussionmentioning
confidence: 99%
“…The examinations and treatments of GBM are expensive and represent a significant economic burden on health care system all around the world 47 . Compare with liquid biopsy, molecular test, and advanced magnetic resonance imaging (MRI) examination, blood biomarkers such like AAPR, NLR, platelet to lymphocyte ratio (PLR), and lymphocyte to monocyte ratio (LMR) are convenient, cheap, and time-saving.…”
Section: Discussionmentioning
confidence: 99%
“…In actual clinical practice in Japan, 6 treatment cycles of TMZ as speci ed in the protocol reported by Stupp et al [1] is not su cient, and TMZ treatment is actually continued for longer in many cases. In the literature, one report has described administration of TMZ for 101 cycles [24], and another indicated that long-term treatment with TMZ until progression is more cost-effective than a treatment protocol that recommends completion of TMZ treatment after 6 cycles [25]. Many publications have discussed the e cacy of long-term treatment [24,[26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In actual clinical practice in Japan, 6 treatment cycles of TMZ as specified in the protocol reported by Stupp et al [1] is not sufficient, and TMZ treatment is actually continued for longer in many cases. In the literature, one report has described administration of TMZ for 101 cycles [31], and another indicated that long-term treatment with TMZ until progression is more cost-effective than a treatment protocol that recommends completion of TMZ treatment after 6 cycles [32]. Many publications have discussed the efficacy of long-term treatment [31,[33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%